1996
DOI: 10.1111/j.1432-1033.1996.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Developmental and Tissue‐Specific Regulation of Expression of the Genes Encoding Three Members of the Flavin‐Containing Monooxygenase Family of Man, FMO1, FMO3 and FMO4

Abstract: . We present here the isolation of a cDNA for FMO3 of iiian. Thc sequcncc of this cDNA and the atnino acid sequcnce deduced from it differ substantially from those previously reported for this member of the FMO family of man. In addition, we have investigated, by quantitative KNase protection assays, the expression in several foetal and adult human tissues of genes encoding FMOl, FM03 and FM04. Our results demonstrate that, in the adult, FMOI is expressed in kidney hut not in livcr, whcrcas in the foetus it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
104
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 36 publications
3
104
4
Order By: Relevance
“…Of the FMOs involved in drug metabolism, FMO3 is the main form present in the adult human liver [12,13,32], which is not the case in other mammals investigated. The age at which the gene is switched on varies from birth to up to two years old, but by 10 months of age most individuals are expressing the enzyme [36].…”
Section: Tissue Distribution and Regulation Of Expressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the FMOs involved in drug metabolism, FMO3 is the main form present in the adult human liver [12,13,32], which is not the case in other mammals investigated. The age at which the gene is switched on varies from birth to up to two years old, but by 10 months of age most individuals are expressing the enzyme [36].…”
Section: Tissue Distribution and Regulation Of Expressionmentioning
confidence: 99%
“…Thus, in the adult human FMO1 makes no contribution to the hepatic metabolism of drugs. The lack of FMO1 expression in adult human liver [12,[31][32][33]36] is in contrast to all other mammals investigated, in which FMO1 represents a major hepatic form of the enzyme. LINE-1 elements upstream of the core liver promoter of FMO1 act as powerful transcription repressors, which might account for the silencing of the gene in the adult human liver [37].…”
Section: Tissue Distribution and Regulation Of Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in our laboratory have observed that FMO1 catalyzed the sulfoxidation of carbamate and organophosphate pesticides much more efficiently than FMO3 (Schlenk et al, 2002;Furnes and Schlenk, 2004). In adult humans, FMO3 is the major liver isoform, and FMO1 primarily is found in kidney and intestines (Dolphin et al, 1996;Overby et al, 1997;Yeung et al, 2000). Thus, the contribution of the FMO system to hepatic organophosphate metabolism is thought to be modest.…”
mentioning
confidence: 99%